Papers development from blending of different natural fibers and nanocellulose addition - Pego, Matheus Felipe Freire (2020)
The pulp and paper industry currently have several challenges that must be overcome, as well as goals that must be reached, whether productive, environmental or related to quality. The product quality is one of these challenges, especially for special or superior papers, with specific properties for a particular use. In this sense, we seek for development of new products to meet market demands. Thus, this study aimed to develop superior papers by mixture of natural fibers obtained from different raw materials and by addition of micro / nanofibrils of cellulose, as well as to understand how these two factors affect the paper quality. Then, samples of cellulosic pulp from sisal, eucalyptus and pine were used. Morphological analyzes of these fibers were performed. The pulps were mixed in different combinations and proportions (5/95%, 25/75% 45/55%,), and destined to the paper production. Virgin papers (100% of each pulp) were also produced. The addition of sisal nanocellulose was performed by two methods: mixing during handsheet formation - MT- (3, 5 and 10% nanofibrils) and surface coating of formed papers -CT- (10% nanofibrils). The reinforced and unreinforced papers were submitted to mechanical, physical and optical tests, besides the structure analysis, spectroscopic and bond strength. For a better understanding of results and conclusions, the thesis was divided into three topics: I - Effects of different fibers blending on the physical-mechanical properties; II - Effects different fibers blending in optical, structural and bond strength properties; and III - Impact of nanocellulose addition on mixed papers. In topic I, it was observed that statistical differences occurred between treatments for physical-mechanical properties and these were related to fiber morphology. The paper thickness tended to decrease with the fiber blend. Lowest mechanical strengths were related to eucalyptus fiber and its mixtures while highest were related to sisal and pine. The addition of small amounts of sisal in mixtures significantly contributed to the improvement of mechanical properties, evidencing the synergistic effect of fiber blending. In topic II, treatments with eucalyptus presented higher bond strength, brightness and air permeability. Mixed papers had better physical properties than virgin papers, evidenced by structural differences in electronic images. In topic III, the addition of nanofibrils to mixed papers increased thickness, volume, weight, apparent density, opacity, roughness, all mechanical properties and reduced bulk, brightness and air permeability. The addition of nanofibrils was different between the two reinforcement methods. The MT method promoted mechanical properties improvement as nanocellulose content was increased. Papers obtained from CT method presented lower mechanical strength values compared to the MT method. Finally, it is concluded that both the mixing of different fibers and the addition of nanofibrils contribute to the improvement of paper quality properties and can become potential methods for high quality paper production or even to increase the added value of these products.